Identification Of Communication Flows And Information Distribution In The Manufacturing Project Control Division Of PT XYZ - Nadyaputri Majid, Audy; Sagita, Leni (International Journal of Science, Technology & Management, 2024)
PT XYZ has four divisions: sales, implementation, planning and evaluation, and finance. As time goes by, there is a recurring phenomenon/case, namely delays in the information distribution process in each division due to ineffective communication flow procedures. Each division has an ongoing distribution of information that is not integrated and can only be accessed by the respective division's personnel. This greatly affects the company directly and indirectly. In this research, the flow of communication at PT XYZ and stakeholders will be identified, as well as the roles and responsibilities of each division personnel at PT XYZ to improve effective and efficient work. The research results also emphasize the communication flow of each division so that each party fully understands the distribution of information to carry out ongoing project implementation at PT XYZ.